Ethics, moral and moralization: Sustainability in food education. (1st December 2020) - Wistoft, Karen
How do you teach sustainability in food education? By preaching and giving lectures? Or by supporting the reflexive capacities of students? It is the opinion of this article that teaching taste and food design with regard to sustainability must be ethically reflexive. We should not moralize. Focusing on sustainability as a reflexive concept, students should not only learn to eat what is deemed to be the right things to eat; they must also learn to relate to food and meals in a critical and informed way. The article points out what 'damage' moralization can do if food and sustainability are designed or communicated without ethical reflections.